(untitled) (INNOVATIVE ECONOMY, 2021)
Halas L.I. STRATEGY OF FOREIGN ECONOMIC ACTIVITY OF AGRICULTURAL ENTERPRISES: CONCEPT AND ITS MAIN FUNCTIONS Purpose. The aim of the article is to research the main interpretations of the definition of “strategy of foreign economic activity” and derivation of the optimal meaning of this concept for agricultural enterprises on the basis of functions performed by the strategy for efficient and competitive entry into foreign markets and further activity of these enterprises in the market. Methodology of research. The following general scientific methods are used in the research process: historical and genetic, statistical and method of analysis and synthesis ‒ to study the theoretical foundations of the strategy of foreign economic activity in the field of agriculture of Ukraine; comparison, description and generalization ‒ to determine the functions of the strategy of foreign economic activity of agricultural enterprises. Findings. The main approaches to the concept of “strategy of foreign economic activity of the enterprise” are studied. The concept of “strategy of foreign economic activity of agricultural enterprises” is developed and substantiated and its main functions for the effective functioning of the agricultural enterprise in foreign markets of goods and services are derived. Originality. Own interpretation of the concept of “strategy of foreign economic activity” is proposed. It should be understood as an effective tool for the enterprise to enter foreign markets of goods and services, which will ensure the implementation of any type of foreign economic activity based on legislation of trade countries and basic strategic management methods on the development of the internal and external environment of the enterprise in order to establish partnerships and trade relations and increase competitive advantages. Practical value. The obtained results of the research are the basis for solving the strategic tasks of agricultural enterprises of Ukraine and are aimed at optimizing the strategic development of enterprises. Key words: strategy of foreign economic activity, agricultural enterprises, functions of strategy of foreign economic activity, planning, control, motivation.